Incentives and innovation: evidence from CEO compensation contracts - Bill Francis; Iftekhar Hasan; Zenu Sharma (Bank of Finland, 2011)
We investigate the relationship between chief executive officer (CEO) compensation and innovation. In an empirical examination of compensation contracts of S&P 400, 500, and 600 firms we find that long-term incentives in the form of options are positively related to patents and citations to patents. In addition, convexity of options has a positive effect on innovation. We also find no relationship between pay for performance sensitivity (PPS) with patents and citations to patents while we did discover a positive relationship between these and golden parachutes. Finally, we show that subsequent to project failure managers compensation contracts are reset favourably. We provide support for the theory that compensation contracts that offer long-term commitment and protection from failure are more suitable for innovation
URN:NBN:fi:bof-20140807365
Keywords: 330